Diagnostic Value of Micropure Imaging Combined with Strain Elastography in Correcting Artificial Intelligence S-Detect Technology for Benign and Malignant Breast Complex Cystic and Solid Masses - Jie YUAN; Cheng WANG; Yingfen DA (Zhongguo yiliao qixie zazhi)
ObjectiveTo explore the diagnostic value of micropure imaging (MI) combined with strain elastography (SE) in correcting artificial intelligence (AI) S-Detect technology for benign and malignant breast complex cystic and solid masses. MethodsThe S-Detect diagnosis results were corrected based on the manifestations of MI and SE of the 145 breast complex cystic and solid masses. Postoperative pathological results were used as the gold standard to calculate the diagnostic sensitivity, specificity, and accuracy before and after correction. Additionally, receiver operating characteristic (ROC) curves were drawn for both groups, and the areas under the curves were compared. ResultsThere were 80 benign and 65 malignant pathological results. After the correction of S-Detect, the diagnostic sensitivity, specificity, and accuracy, as well as the areas under the ROC curves, were all improved compared to before the correction. ConclusionCombining MI and SE to correct the diagnostic results of S-Detect can help improve the diagnostic efficacy of breast complex cystic and solid masses.